2009
DOI: 10.1111/j.1439-0396.2008.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and gene expression of porcine fatty acid transport protein 1 isoforms

Abstract: Fatty acid transport protein 1 (FATP-1) is a membrane associated protein, which facilitates the long chain fatty acids (LCFA) transport across the plasma membrane for the LCFA utilization and storage. In this study, the cDNA structure of porcine FATP-1 was investigated and the gene expression patterns of porcine FATP-1 in different tissues were tested by RT-PCR and Southern blot analysis. The results showed that there were five pFATP-1 mRNA species, namely, FATP-1a, FATP-1aV, FATP-1b, FATP-1c and FATP-1cV and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Kidney, skin, eye, muscle and heart also had relatively high levels of FATP1b gene expression. Although different splicing variants of FATP1 have been reported in mammals and birds (Shu et al., ), this is the first time to clone a different subtype of FATP1. The different tissue distribution pattern between FATP1a and FATP1b indicates the probable function diversification between these two FATP1 subtypes, which may result from the diversification in fatty acid preference.…”
Section: Resultsmentioning
confidence: 83%
“…Kidney, skin, eye, muscle and heart also had relatively high levels of FATP1b gene expression. Although different splicing variants of FATP1 have been reported in mammals and birds (Shu et al., ), this is the first time to clone a different subtype of FATP1. The different tissue distribution pattern between FATP1a and FATP1b indicates the probable function diversification between these two FATP1 subtypes, which may result from the diversification in fatty acid preference.…”
Section: Resultsmentioning
confidence: 83%
“…SLC27A1 is also called fatty-acid transport protein-1 (FATP-1). Members of this transport family play an important role in the uptake of long-chain fatty acids into mammalian cells as integral transmembrane proteins [69,70] and have unique expression patterns [71,72,73]. Previous studies in pigs suggested that FATP-1 plays a role in fatty-acid utilization in muscles, especially red muscle tissues, rather than a role in fat storage in adipose tissues [38,74,75,76].…”
Section: Discussionmentioning
confidence: 99%
“…ATPase and the sodium/hydrogen exchanger ( NHE3 ) are responsible for the absorption of nutrients including fatty acids, AA, and glucose. , AA transporters and the intestinal peptide transporter are identified as seven systems and play important transport activities and functions on FAA and small peptide . Apolipoprotein A1 ( APOA1 ) and fatty acid transport protein ( FATP-1c ) is involved in plasma triglyceride metabolism by activating lipoprotein lipase and mediates transport of aliphatic acids, respectively . The facilitated glucose transporter GLUT2 and the sodium-glucose cotransporter SGLT-1 mediates glucose transport in intestinal epithelial cells .…”
Section: Introductionmentioning
confidence: 99%
“…11 Apolipoprotein A1 (APOA1) and fatty acid transport protein (FATP-1c) is involved in plasma triglyceride metabolism by activating lipoprotein lipase and mediates transport of aliphatic acids, respectively. 12 The facilitated glucose transporter GLUT2 and the sodium-glucose cotransporter SGLT-1 mediates glucose transport in intestinal epithelial cells. 13 In addition, AA affects both nutrient transport and protein synthesis by activating the mammalian target of rapamycin complex 1 (mTORC1) and its downstream targets S6 kinase 1 (S6K1) and the initiation factor 4E binding protein (4E-BP1).…”
Section: ■ Introductionmentioning
confidence: 99%